A Longitudinal Study of Age‐Related Differences in Reactions to Psychological Contract Breach. Issue 1 (22nd August 2012) - Bal, P. Matthijs; De, Annet H.; Jansen, Paul G.W.; Van Der, Mandy E.G.
<x xml:space="preserve">Abstract</x> The current paper investigated age‐related differences in the relations of psychological contract breach with work outcomes over time. Based on affective events theory, we expected job satisfaction to mediate the longitudinal relationship of contract breach with changes in job performance. Moreover, based on socio‐emotional selectivity theory, it was predicted that reactions to contract breach on job satisfaction and job performance would be stronger among younger workers than older workers. This two‐wave panel study among 240 employees investigated interactions of age with psychological contract breach in relation to changes in job satisfaction and job performance over time. Moderated structural equation modeling showed that job satisfaction partially mediated the longitudinal relationships between contract breach and job performance. Moreover, the analyses supported socio‐emotional selectivity theory; older workers reacted less intensely to psychological contract breach towards job satisfaction and job performance, indicating a general decreased responsiveness of older workers towards the psychological contract. It is concluded that age plays an important role in how contract breaches relate to changes in work outcomes over time.